DAKWAH MELALUI JURNAL - Iskandar Iskandar (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
Jurnalism is a printing media in the writing form not form only of news impormation, but it is colored also with writing anyelse that has double characters, as giving impormation and can comfort. The religion leaders has opportunity to write their imajination in the accurate of lifing development in their around. Who can be published by jurnalistic. The idea that return problems to creat religion shape as a truthfull religion that bringing peacefully world (rahmatan lil alamina). This is as contribution that most valuable for giving solutions in the people life.